Transcriptome profiling the gills of amoebic gill disease (AGD)-affected Atlantic salmon (Salmo salar L.): a role for tumor suppressor p53 in AGD pathogenesis - Morrison, RN; Cooper, G; Koop, B; Rise, M; Andrew Bridle; Mark Adams; Barbara Nowak (2006)
Neoparamoeba spp. are amphizoic amoebae with the capacity to colonize the gills of some marine fish, causing AGD. Here, the gill tissue transcriptome response of Atlantic salmon (Salmo salar L.) to AGD is described. Tanks housing Atlantic salmon were inoculated with Neoparamoeba spp. and fish sampled at time points up to 8 days postinoculation (pi.). Gill tissues were taken from AGD-affected fish, and a DNA microarray was used to compare global gene expression against tissues from AGD-unaffected fish. A total of 206 genes, representing 190 unique transcripts, were reproducibly identified as up- or downregulated in response to Neoparamoeba spp. infection. Informative transcripts having GO biological process identifiers were grouped according to function. Although a number of genes were placed into each category, no distinct patterns were observed. One Atlantic salmon cDNA that was upregulated in infected gill relative to noninfected gill at 114 and 189 h pi. showed significant identity with the Xenopus, mouse, and human anterior gradient-2 (AG-2) homologs. Two Atlantic salmon AG-2 mRNA transcripts, designated asAG-2/1 and asAG-2/2, were cloned, sequenced, and shown to be predominantly expressed in the gill, intestine, and brain of a healthy fish. In AGD-affected fish, differential asAG-2 expression was confirmed in samples used for microarray analyses as well as in AGD-affected gill tissue taken from fish in an independent experiment. The asAG-2 upregulation was restricted to AGD lesions relative to unaffected tissue from the same gill arch, while p53 tumor suppressor protein mRNA was concurrently downregulated in AGD lesions. Differential expression of p53-regulated transcripts, proliferating cell nuclear antigen and growth arrest and DNA damage-inducible gene-45Î² (GADD45Î²) in AGD lesions, suggests a role for p53 in AGD pathogenesis. Thus AGD may represent a novel model for comparative analysis of p53 and p53-regulated pathways. Copyright Â© 2006 the American Physiological Society.